Rāhnamā-yi dastnivishthā-yi Mānavi-yi Tūrfān (ravish shināsi-yi vīrāyish va bāz sāzī) - Shukrī-Fūmishī, Muḥammad (Miras Maktoob, ISBN: 9789004365452., 2019)
After its foundation by Mani in the third century CE, Manicheism spread quickly from Iran through the ancient world, from North Africa to Europe and from Central Asia to China. Mani wrote seven works, six in Syriac and one in Middle Persian. The spread of Manicheism led to the emergence of Manichean writings in a number of other languages, and also of texts in criticism or description of this religion by non-Manichean authors in some of these same languages, among them Greek, Latin, Coptic, Arabic, Soghdian, and Chinese. From among the archeological findings involving Manichean texts, one of the most exciting ones was the discovery, in the early nineteen hundreds, of many Manichean fragments in Turfan, in Xinjiang province, China. These are in Middle Persian, Parthian, Soghdian and Manichean New Persian, besides material in Uygur, Bactrian and Kuchean. The present work is a Persian manual for the interpretation, reconstruction and edition of these Turfan texts.